ANALISIS KORELASI PEARSON UNTUK UNSUR-UNSUR KIMIA AIR HUJAN DI BANDUNG - Tuti Budiwati; Afif Budiyono; Wiwiek Setyawati; Asri Indrawati (Lembaga Penerbangan dan Antariksa Nasional, 2010)
Pearson correlation coefficients are used to study influences of chemical and meteorological factors to rain water characteristic. The chemical composition of rain water analysis is composed of anion variables such as sulphates (SO42-), nitrates (NO3-), chlorides (Cl-), and cation variables such as ammonium (NH4+), calsium (Ca2+), kalium (K+), sodium (Na+) and magnesium (Mg2+). Furthermore, other active variables such as pH and electric conductivity (EC) influences are also assessed. The statistical analysis is used to obtain a more comprehensive assessment in order to understand acid rain events. The acid rain is often correlated to strong meteorological factor influences such as rainfall. Therefore, the study is carried out for two different seasons in Bandung, i.e. wet and dry seasons.Keywords: Anion, Cation, Electric conductivity (EC), Pearson correlation coefficient, pH